Через время, через океан - Литвинова Анна Витальевна (Две звезды российского детектива, 2009)
Экземпляры: ф.5,ЦБ (20091030) / Инвентарный номер: 42004 / Цена: 141.40 / Авт.знак: Л 64 / ББК: 84(2Рос=Рус)6